Formação continuada com professores que ensinam matemática : uma abordagem sobre o uso de material didático manipulável - Silva, Lais Scorziello Feitosa da (2024)
Several educators have cited the importance of teaching progressing from the tangible to the abstract; hence, this research highlights the importance of using manipulable didactic materials (MDM) in mathematics teaching. It is claimed that the correct use of MDM promotes meaningful learning for students, in addition to developing logical, critical, and scientific reasoning. However, it is emphasized that MDM alone will not ensure that students understand the intended mathematical concepts, and for this to occur, the teacher's mediation becomes crucial. Furthermore, for the use of MDM in the classroom, it is essential that the teacher knows the chosen material and is able to organize a dynamic that promotes learning. Considering that the use of MDM in teaching is important and that the effectiveness of these resources depends more on the educator than on the material itself, the relevance of continuous training (CT) courses that assist teachers in this process becomes evident. Therefore, a CT course was developed with teachers who teach mathematics in the municipality of Piúma-ES, focusing on the use of MDM in teaching. In light of this, the objective of the research, with a qualitative and participatory approach, was to investigate whether a CT course related to teaching through the use of MDM contributes to what teachers who teach mathematics in schools in the municipality of Piúma-ES know and think. The developed CT course took place between August and October 2023, with 13 participants. The data collection instruments included questionnaires, discussion circles, and a field journal. It was found that the participating teachers were already using some MDM, recognized the importance of these resources for their students, but were eager to learn about other materials. Despite facing some challenges regarding the use of MDM, such as lack of resources, the need for more planning time, and large class sizes, the teachers used some materials during the CT course with their classes and were surprised by the positive results. Some shifts in perspectives regarding the use of MDM in mathematics teaching were observed. Some participants recognized the importance of MDM for fostering dialogue during the knowledge construction process, while others continued to use the materials. Additionally, changes in thinking about how to use MDM were identified, in order to better leverage the potential of the materials. Therefore, the need for the provision of CT courses focused on the use of MDM in mathematics teaching, as well as improving the teacher's work environment, is understood